Materialism in Works by I.P. Pnin and P.-H.T. Holbach: Comparative Analysis - SMIRNOV, Dmitry; MASLOVA (IVANOVA), Anna (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The authors study the process of perception of the materialistic ideas promoted by the French Enlightenment over the period of the emergence of early Russian liberalism. The article focuses on the specific features of perception and promotion of the materialistic worldview, including P.-H.T. Holbach’s ideas presented in the works by I.P. Pnin, who was one of the brightest social thinkers in Russia at the turn of the 19th century. First and foremost, the authors examine the activity conducted by Pnin in the context of St. Petersburg Journal (1798) he published, which featured the most progressive ideas of that time.RESUMEN Los autores estudian el proceso de percepción de las ideas materialistas promovidas por la Ilustración francesa durante el período del surgimiento del liberalismo ruso temprano. El artículo se centra en las características específicas de la percepción y la promoción de la cosmovisión materialista, incluido P.-H.T. Las ideas de Holbach presentadas en los trabajos de I.P. Pnin, quien fue uno de los pensadores sociales más brillantes de Rusia a principios del siglo XIX. En primer lugar, los autores examinan la actividad realizada por Pnin en el contexto del St. Petersburg Journal (1798) que publicó y presentaba las ideas más progresistas de la época.